Optimizing The Role of The Community in Ecosystem Resource Management to Reduce Stunting Rates in Baumata Timur Village (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake over a long period of time as a result of the provision of food that does not meet nutritional requirements and occurs from the fetus is still in the womb as well as newly appeared when the child is two years old. The purpose of the activities is to increase the participation of the community in the management of ecosystems in East Baumata Village, Kupang District, East Nusa Tenggara. The methods used are surveys and observations. The result of this activity is increased knowledge and understanding of the community of East Baumata Village about how to treat the ecosystem well and properly to deal with the problem of stunting, as well as increasing knowledge and skills for pregnant mothers or nursing babies about the importance of healthy foods and containing a lot of protein for the growth and development of children and breast-feeding accompanying food (MPASI).
Keywords: Stunting; MPASI; Ecosystem Management; Baumata Community